Stratyfikacja warstw wyższych w dawnej Polsce (ziemiaństwo i arystokracja) - Kwilecki, Andrzej (Wydział Prawa i Administracji UAM, 1996)
The term "the gentry", denoting owners of farms and large estates, had been introduced in the 19th cent, to replace the term "nobility". At the same time the notion of "aristocracy" came to describe this section of the landed gentry who possessed the biggest estates and hereditary titles - mostly princes and counts. The paper presents a survey of the issues - research-wise, sociological and historical - concerned with (a) definition of gentry and aristocracy, (b) delineation of their social structure and inner differentiation, (c) demarcation of the line dividing aristocracy from the rest of the society, and (d) explication of factors which ensured the aristocrats' highest position in the hierarchy of social prestige throughout the historical period up to the Second World War. The author discusses briefly literature in genealogy, sociology, history and memoirs writing, and indicates a remarkable phenomenon of the recent years (following 1989): an eruption of the reading public's interest in the issues in question and an avalanche of publications focused on the past and recent history of the Polish gentry and aristocracy.
Stratigraphy of the upper classes in Poland of the past (gentry and aristocracy